العلاقة بين رأس المال الفكري وريادة الأعمال في الجامعات الخاصة بمدينة بنغازي دراسة ميدانية على الجامعة الليبية الدولية للعلوم الطبية (Economic studies journal, 2019)
The study aims to addressing and defining the concept of intellectual capital and its relation to entrepreneurship in business organizations. Also, to identify the reality of the performance of educational institutions in Benghazi and assess the level of interest in the requirements of the transition to the adoption of intellectual capital as one of the elements of important assets. In addition to reaching results that may help to achieve entrepreneurship for the study sample as well as provide a proposed vision for development. The study population included the members of the teaching staff of the medical colleges at the Libyan of Medical Sciences University for the period from May to August 2018. The data for this study were collected by distributing a questionnaire form on a random sample of the study population. The study variables included intellectual capital in its three components as an independent variable, and entrepreneurship as a dependent variable. The statistical program SPSS was also used to analyze the data obtained. The results showed that there is a statistically significant correlation between intellectual capital and entrepreneurship, which led to acceptance of the null hypothesis and rejection of the alternative hypothesis. The study also recommended expanding the study to include the other private universities in Libya, as well as conducting such studies to include Libyan business organizations. In addition, to employing intellectual capital components in business organizations more effectively, in order to enhance their positive impact in achieving entrepreneurship.
Keywords: Entrepreneurship, Intellectual Capital; Business Organizations; Private Universities